2009
DOI: 10.1258/jms.2009.009062
|View full text |Cite
|
Sign up to set email alerts
|

Article Commentary: The contributions of Louis I Woolf to the treatment, early diagnosis and understanding of phenylketonuria

Abstract: Early diagnosis of phenylketonuria (PKU) became a goal worth pursuing following demonstration of the efficacy of the dietary treatment conceived by Louis I Woolf. This paper narrates the history of this treatment, describes Woolf's role in the establishment of neonatal PKU screening and surveys his other contributions to our understanding of this condition. If Woolf, Centerwall, Baird and Berry had waited until all the scientific evidence about PKU that is now at our disposal had been brought to light, there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 60 publications
(95 reference statements)
0
7
0
5
Order By: Relevance
“…In 1951, Louis Woolf demonstrated that the chemical phenotype of PKU responded to the dietary restriction of phenylalanine (Cf. Alonso‐Fernández & Colón, for a review), and was subsequently shown by Dobson, Kushida, Williamson, and Friedman () to improve cognitive function as expressed by increased IQ scores. Subsequently, haploinsufficiency of the gene, PAH , was found to produce PKU (Ledley, Grenett, DiLella, Kwok, & Woo, ), thus establishing a genotype‐phenotype relationship.…”
Section: Introductionmentioning
confidence: 91%
“…In 1951, Louis Woolf demonstrated that the chemical phenotype of PKU responded to the dietary restriction of phenylalanine (Cf. Alonso‐Fernández & Colón, for a review), and was subsequently shown by Dobson, Kushida, Williamson, and Friedman () to improve cognitive function as expressed by increased IQ scores. Subsequently, haploinsufficiency of the gene, PAH , was found to produce PKU (Ledley, Grenett, DiLella, Kwok, & Woo, ), thus establishing a genotype‐phenotype relationship.…”
Section: Introductionmentioning
confidence: 91%
“…These assays were employed in 1978 in Santiago de Compostela (Galicia) when introducing neonatal screening. For various reasons, Woolf’s original methodology was adapted (see e.g., reference [ 20 , 21 ]). Other assays (e.g., a cystine/homocystine test or Brand’s test) were performed in the same way as Woolf suggested.…”
Section: Woolf’s Interactions With Spanish Investigatorsmentioning
confidence: 99%
“…This paper also tries to acknowledge just that. This paper deals with only part of Dr. Woolf’s work; for further reading see [ 20 , 21 ].…”
Section: Epiloguementioning
confidence: 99%
“…Poco tiempo después publicó sus hallazgos, denominando imbecillitas phenylpyruvica a la enfermedad de estos niños y postulando que podía estar relacionada con un error en el metabolismo del aminoácido fenilalanina. Así fue la primera vez que se asoció la deficiencia mental con un ECM, el conocido como "oligofrenia fenilpirúvica", "enfermedad de Følling" o, más tarde, PKU (por la presencia en orina de fenilacetona) [24][25][26] . En 1951, el bioquímico inglés Louis I. Woolf sugirió en un artículo que el fallo intelectual de los fenilcetonúricos era debido a una intoxicación por ácido fenilacético y apuntaba a la reducción de fenilalanina en la ingesta como posible tratamiento: "Si la cantidad de fenilalanina y sus productos de degradación pueden reducirse, la función cerebral podrá resultar normal, el que esto lleve a la recuperación o no probablemente dependerá de la duración de la exposición del cerebro a la concentración dañina de la sustancia.…”
Section: Origen De Los Programas De Cribado Neonatalunclassified